Recent developments and results of the LPSC PHOENIX type ECR charge breeder. Issue 1 (1st April 2022) - Angot, J; Baylac, M; Luntinen, M; Migliore, M; Tarvainen, O; Thuillier, T
Abstract: Four models of the PHOENIX ECR charge breeder have been manufactured for ISOL application. Two are currently under operation at TRIUMF (ISAC) and GANIL (SPIRAL 1) while the SPES one is being installed on the facility. The last model is set on the LPSC 1+N+ test bench where a R&D program is ongoing to improve its performances. The last modifications consisted in improving the beam line vacuum and the alignment. Commissioning experiments showed an improvement of the charge breeder performances for all the tested species. The global CB efficiency is close to 100% for Cs when correcting the measurements with the beam transmission. Na and K efficiencies have increased significantly to reach 18.7% for Na 8+ and 22.7% for K 9+ . In parallel, the charge breeder plasma was studied injecting short pulses of 1+ ions and using a zero-dimension model to estimate the plasma parameters. These experiments have provided a better understanding of the performance improvement. The last developments of the LPSC Charge Breeder together with the experimental results are presented.